Srategi Branding Melalui Inovasi Produk Dan Kemasan Minuman Herbal Instant UMKM Kendijati – CV. Ning Saudah - Septi Calista Nanda; Shaluna Mei Ardhana; IGN. Anom Maruta (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
MSMEs Ning Saudah is an instant herbal medicine product business located on Jalan Penjaringan Sari, Rungkut District, Surabaya. The owner of the business is named Nur Saudah. This research explores the role of product and packaging innovation in improving branding in Micro, Small and Medium Enterprises (MSMEs) in the instant herbal beverage sector, with a focus on the case study of MSME